Donor Haplotype B of NK KIR Receptor Reduces the Relapse Risk in HLA-Identical Sibling Hematopoietic Stem Cell Transplantation of AML Patients - Impola, Ulla; Turpeinen, Hannu; Alakulppi, Noora; Linjama, Tiina; Volin, Liisa; Niittyvuopio, Riitta; Partanen, Jukka; Koskela, Satu (Frontiers in Immunology, 2014)
Successful allogeneic hematopoietic stem cell transplantation (HSCT) depends not only on good HLA match but also on T-cell mediated graft-versus-leukemia (GvL) effect. Natural killer (NK) cells are able to kill malignant cells by receiving activation signal from the killer-cell immunoglobulin-like receptors (KIR) recognizing HLA molecules on a cancer cell. It has been recently reported that the risk of relapse in allogeneic hematopoietic stem cell transplantation (HSCT) is reduced in acute myeloid leukemia (AML) patients whose donors have several activating KIR genes or KIR B-motifs in unrelated donor setting, obviously due to enhanced GvL effect by NK cells. We studied the effect on relapse rate of donor KIR haplotypes in the HLA-identical adult sibling HSCT, done in a single center, in Helsinki University Central Hospital, Helsinki, Finland. Altogether, 134 patients with 6 different diagnoses were identified. Their donors were KIR genotyped using the Luminex and the SSP techniques. The clinical endpoint, that is, occurrence of relapse, was compared with the presence or absence of single KIR genes. Also, time from transplantation to relapse was analyzed. The patients with AML whose donors have KIR2DL2 or KIR2DS2 had statistically significantly longer relapse-free survival (P = 0.015). Our data support previous reports that donors with KIR B-haplotype defining genes have a lower occurrence of relapse in HSCT of AML patients. Determination of donor KIR haplotypes could be a useful addition for a risk assessment of HSCT especially in AML patients.